Melanin-Aware and ArcFace Methods in Facial Recognition for Dark-Skinned Individuals - Risa Tioria Marlini Purba; Fadhil Hidayat; Suhono Harso Supangkat; Arry Akhmad Arman (Jurnal Sistem Cerdas, 2025)
The facial recognition system employing the Melanin-Aware method in conjunction with ArcFace, trained on a dataset of 1,000 dark-skinned facial samples, demonstrates the ability to accurately recognize individuals with dark skin while maintaining performance for non-dark-skinned individuals. ArcFace is utilized as the primary feature extractor, leveraging the additive angular margin to enhance inter-class separability. The experiments were conducted using 1,000 dark-skinned facial samples for training and 100 samples for testing. Evaluation results indicate that melanin-aware preprocessing improves average accuracy by up to 17% compared to the absence of preprocessing, and by 7% compared to the standard aggressive CLAHE-based method. Furthermore, the True Acceptance Rate (TAR) increased from 88.15% to 93.33% at FAR = 1e−2, and from 83.7% to 86.67% at FAR = 1e−3, signifying enhanced system stability under stringent security conditions. The performance gains are supported by a more stable distribution of similarity scores and lower threshold values, reflecting improved separation between genuine and impostor pairs.